Banking stability and financial conglomerates in European emerging countries - Vodová, Pavla Klepková; Palečková, Iveta; Stavárek, Daniel (Cambridge : Cambridge University Press, 2022)
This Element focuses on the specific role of financial conglomerates in managing banking and financial stability. The Element aims to estimate financial stability in CEE using the constructed aggregate financial stability index, to incorporate the financial stability of the parent company into the index, and to assess the effect of the parent company on the financial stability of commercial banks and national financial sectors.
Title from publisher's bibliographic system (viewed on 16 Dec 2022).
Keywords: elektronické knihy; electronic books; Banks and banking -- Europe, Central; Banks and banking -- Europe, Eastern; Conglomerate corporations -- Europe, Central; Conglomerate corporations -- Europe, Eastern